Evaluating The Study of Language by George Yule for Linguistic Education in Pakistani Universities: Cultural Relevance and Pedagogical Impact - Malik, Muhammad Zeeshan Akram; Kharal, Ali Ahmad; Jalall , Muhammad Akbar (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the effectiveness and appropriateness of George Yule's The study of language (7th Edition) in Pakistani linguistic education. Using a mixed-methods approach, the current study combines textual analysis with a survey of both faculty members and students who have used this textbook in BS English programs in Pakistan. The findings further explain the potential strengths of the book in terms of the introduction of linguistic concepts but reflect its limitations in terms of cultural relevance and accessibility to diverse populations of students. This study offers actionable insights toward making linguistic resources more inclusive for Pakistani learners in terms of analyzing comments about content clarity, implications for pedagogy, and suggestions for improving support in instruction.